2003
DOI: 10.1007/s00216-002-1676-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ultratrace elements in natural waters by solid-phase extraction and atomic spectrometry methods

Abstract: A study was carried out on the preconcentration of ultratrace amounts of cadmium, lead, manganese, copper and iron from high-salinity aqueous samples and determination by atomic spectrometry methods. Sample volume, amount of resin, loading flow rate, and elution volume were optimized in order to obtain the simultaneous preconcentration of all the analytes. Quantitative recoveries were obtained by using 200 mg of iminodiacetic resin with a loading flow rate of 2 mL min(-1), elution volume of 3 mL and sample vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It took 60 min at 130 o C to complete decomposition of the substance. minerals, rocks) with tellurium content 0.0-100 mg g -1 , [24], coal, [25], in lead and lead alloys [26], in the environment (water, plants, biological materials) [27][28][29]. Such techniques as atomic emission spectrometry (AES) with inductively coupled (ICP) or microwave (MP) plasma, in conjunction with mass spectrometry, [30][31][32][33], atomic fluorescence spectrometry, [34][35][36], the optical emission spectrometry [37] are used for the tellurium and tellurium trace analysis in various objects.…”
Section: Procedures For the Decomposition Of Tellurium-containing Orgmentioning
confidence: 99%
“…It took 60 min at 130 o C to complete decomposition of the substance. minerals, rocks) with tellurium content 0.0-100 mg g -1 , [24], coal, [25], in lead and lead alloys [26], in the environment (water, plants, biological materials) [27][28][29]. Such techniques as atomic emission spectrometry (AES) with inductively coupled (ICP) or microwave (MP) plasma, in conjunction with mass spectrometry, [30][31][32][33], atomic fluorescence spectrometry, [34][35][36], the optical emission spectrometry [37] are used for the tellurium and tellurium trace analysis in various objects.…”
Section: Procedures For the Decomposition Of Tellurium-containing Orgmentioning
confidence: 99%
“…By ranking the measured tin contents and the sampling sites it can be observed that samples which show the concentration above the median values (No. 4,6,8,7,15,1,13,2) were collected from sites near aluminium processing industry centre, harbours, and fishing ports.…”
Section: Analysis Of Shell Samplesmentioning
confidence: 99%
“…1 Analytical performances of inductively coupled plasma atomic emission spectrometry (ICP-AES) allow simultaneous measurements of numerous elements and more emission lines of the particular element. However, interference effects in direct measurements of real sample solutions were not avoided completely, especially those caused by complex matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the biological and chemical processes effecting iron distribution and cycling in coastal environments, there is an urgent need to develop simple analytical tools specically designed to determine the total dissolved iron in coastal waters. To achieve this goal, many techniques have been developed to detect and quantify iron such as atomic absorption spectrometry (AAS), 10 inductively coupled plasma-mass spectrometry (ICP-MS), 11,12 electrothermal atomic absorption spectrometry (ETAAS), 13 and spectrophotometry. 14 However, these methods are relatively expensive for the ultra-trace determination of iron and can suffer from interferences.…”
Section: Introductionmentioning
confidence: 99%